An Integration of Genome-Wide Association Study and Gene Co-expression Network Analysis Identifies Candidate Genes of Stem Lodging-Related Traits in Brassica napus - Li, Hongge; Cheng, Xi; Zhang, Liping; Hu, Jihong; Zhang, Fugui; Chen, Biyun; Xu, Kun; Gao, Guizhen; Li, Hao; Li, Lixia; Huang, Qian; Li, Zaiyun; et al. (Frontiers in Plant Science, 2018)
Lodging is a persistent problem which severely reduce yield and impair seed quality in rapeseed (Brasssica napus L.). Enhancing stem strength has proven to be an effective approach to decrease lodging risk. In the present study, four interrelated stem lodging-related traits, including stem breaking resistance (SBR), stem diameter (SD), stem strength (SS) and lodging coefficient (LC), were investigated among 472 rapeseed accessions. A genome-wide association study (GWAS) using Brassica 60K SNP array for stem lodging-related traits identified 67 significantly associated quantitative trait locus (QTLs) and 71 candidate genes. In parallel, a gene co-expression network based on transcriptome sequencing was constructed. The module associated with cellulose biosynthesis was highlighted. By integrating GWAS and gene co-expression network analysis, some promising candidate genes, such as ESKIMO1 (ESK1, BnaC08g26920D), CELLULOSE SYNTHASE 6 (CESA6, BnaA09g06990D) and FRAGILE FIBER 8 (FRA8, BnaC04g39510D), were prioritized for further research. These findings revealed the genetic basis underlying stem lodging and provided worthwhile QTLs and genes information for genetic improvement of stem lodging resistance in B. napus.